Phytochemical and Pharmacological Investigations of Uraria lagopodies DC. and Urena lobata L. (Dhaka University Journal of Pharmaceutical Sciences, 2012)
Easy availability and reduced side effects of plants and plant-derived herbal preparations are the gifts of nature and are useful since ancient time for the treatment of various diseases. From this view point twoBangladeshi plants, Uraria lagopodies DC. and Urena lobata L. have been evaluated for their possible pharmacological activities. Preliminary phytochemical screenings with the crude ethanol extracts demonstrated the  presence of alkaloids, glycosides, tannins, saponins, steroids and reducing sugars. The crude extract of U. lagopodies significantly (p